Big Hope Centre / Farinah Saelih ... [et al.] - Saelih, Farinah; Dainal, Nor Alzatie; Mansor, Mohd Firdaus; Said, Norhidayah; Mausi, Ather (2010)
Our company name is Big Hope Centre. We chose this name because it is compatible with the service we provide that care of children who have Down syndrome. This is in line with Malaysia's aspiration is not to ignore people with disabilities (bminggu@bharian.com.my 21/03/2010). For realizing the government's intention that the Down syndrome should be educated, Big Hope Centre want to provide care and special education for Down syndrome in creating a society that can live better. Our target market is people near Kota Kinabalu. This is because according to statistics 1 in 700 births are those which deal with the birth of Down syndrome (the information based on Berita Harian 21/03/2010). Latest information from the Berita Harian (2008) in Kota Kinabalu birth rate was 51,773. We see the total fertility rate is a good potential for us to provide child care services who have down syndrome. Each year the birth rate for urban areas will increase from year to year due to factors of development and migration of rural people. We believe our services can be successful because of the existing services of only one. The support they have approximately 200 children. Our service locations are in Kingfisher because this area is an area where people live. This location is also strategic because it is the middle area between the target market areas.